Tempus Werrae: entre o fazer bélico e a escrita da história em tempos de conflito no Reino Inglês (século XIV) - Santos, Fernando Pereira dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Until the beginning of fourteeth century, chronicle writing in England prevailed under the responsability of religious houses. From this century onwards, however, the ability of writing leaves off the monastic scriptoria, and the handling of the feather will be slowly shared with individuals belonging to the lay world. At this point, it is possible to observe the shifting in the ways of writing history, as the preoccupations of men linked to the lay power bring into the center of the written history a theme that overlaps all others: war, namely that fought against Frenchmen and Scots. If the marvellous and divine actions interspersed such narratives, now the prevailing issues are those concerned to organization and effective action in warfare, taking into consideration the performance of noblemen in both moments. Therefor, this research inquires not only about the mechanisms employed by chroniclers in the attempt to ensure trustworthiness to their reports, but in like manner the diverse roles fourteenth-century chronicle writing played to the contemporary nobility, whose actions were portrayed by them. Bearing in mind such goals, we analyzed lay chronicles composed by Geoffrey le Baker, Jean le Bel and Thomas Gray, men apparently without any proximity, but who shared designs and ideals about both warrior behavior and their practices. When those chronicles are collated among themselves and altogher with other contemporary documents, they do not cover war by itself, as from their perspective of the conflict they offer a wider view of what deserved to be remembered in the kingdom of England in the first phases of the Hundred Years War

Até o início do século XIV, a escrita cronística esteve, na Inglaterra, predominantemente sob a responsabilidade das casas religiosas. A partir desse século, entretanto, o domínio da escrita deixa de estar apenas sob domínio dos scriptoria monacais e a pena passa lentamente também para a mão de indivíduos ligados ao mundo laico. Nessa altura, é possível notar certo deslocamento na forma de se fazer a história, pois as preocupações desses homens ligados ao poder laico trazem ao centro da história escrita um tema que se sobrepõe a todos os outros: a guerra, nomeadamente aquela contra escoceses e franceses. Se antes o maravilhoso e as ações divinas entremeavam tais narrativas, os temas que passam a predominar são aqueles ligados à organização e à realização das atividades bélicas, bem como à atuação da nobreza. Assim, a pesquisa inquire tanto sobre os mecanismos empregados pelos cronistas na tentativa de garantir a credibilidade de seus relatos quanto acerca das funções que a escrita cronística trecentista desempenhou para a nobiliarquia contemporânea, cujas ações descreveu. Tendo em vista esses objetivos, foram tomadas como objetos de análise as crônicas de cunho secular compostas por Geoffrey le Baker, Jean le Bel e Thomas Gray, homens sem aparente contato entre si mas que partilharam concepções e ideais sobre a conduta e as finalidades guerreiras. Quando cotejadas entre si e com outros documentos coetâneos, as crônicas, entretanto, não apenas tratam da guerra, mas a partir dela oferecem um quadro daquilo que merecia memória no reino da Inglaterra nos primeiros tempos da Guerra dos Cem Anos
Keywords: Guerra - Cronicas; Escrita - História; Nobreza; Historiografia; Guerra dos Cem Anos - 1339-1453; Inglaterra - Historia